2013
DOI: 10.7860/jcdr/2013/5831.3841
|View full text |Cite
|
Sign up to set email alerts
|

An In vitro SEM Study on the Effect of Bleaching Gel Enriched with NovaMin on Whitening of Teeth and Dentinal Tubule Occlusion

Abstract: Introduction: Tooth whitening products enjoy substantial popularity. However, tooth hypersensitivity is invariably an undesirable consequence. Desensitizing toothpastes may be used for alleviating the symptoms. NovaMin, as an active ingredient in many dentifrices, has been shown to deliver significant therapeutic desensitising benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…Although some studies shows some substances as gold stantards in occluded tubules, specially Sodium Potassium Phosphosilicate [1,13,15,23,24,26,31,32], in our research all dentifrices were able to occluded dentinal tubules without any statistical difference. It could be seen at SEM images and qualitative analyses.…”
Section: Mean (%) ± Sdcontrasting
confidence: 65%
See 1 more Smart Citation
“…Although some studies shows some substances as gold stantards in occluded tubules, specially Sodium Potassium Phosphosilicate [1,13,15,23,24,26,31,32], in our research all dentifrices were able to occluded dentinal tubules without any statistical difference. It could be seen at SEM images and qualitative analyses.…”
Section: Mean (%) ± Sdcontrasting
confidence: 65%
“…The Calcium Sodium Phosphosilicate (Novamin) produces a form of apatite when in aqueous environment, an effect that is augmented by the presence of smear layer. The Potassium Nitrate, Potassium Citrate, Sodium Monofl uorphosphate, Stronium Clhoride, and Sodium Potassium Phosphosilicate with the use, are deposited inside the dentinal tubules helping to obliterate them [1,3,8,12,13,[22][23][24][25][26][27].…”
Section: Mean (%) ± Sdmentioning
confidence: 99%
“…It was found that the addition of NovaMin to 15% Carbamide peroxide occluded the dentinal tubules and that it did not affect the bleaching procedure. They also emphasized its clinical relevance in a dual advantage of desensitizing and bleaching with a single paste system [32]. Recent studies have also demonstrated a potential for NovaMin to prevent demineralization and/or aid in remineralization of white-spot lesions [23].…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the literature many clinical trials have used NovaMin in dentifrices [23,[29][30][31][32], but very little data is available on application of NovaMin powder directly to tooth structure to relieve dentin hypersensitivity. The use of other desensitizing agents in dentifrices needs frequent applications and use of laser equipment is expensive and requires skilled personnel.…”
Section: Discussionmentioning
confidence: 99%
“…(31) D. Amorphous calcium sodium phosphosilicate (NOVAMIN): It's mechanism action is as effectively delivering silica, calcium, phosphorus and forms an occlusive layer over dentin. Kakodkar G et al in 2013 stated that it has the dual advantage of bleaching and densensitization. (32) Millemann J et al in 2012 stated that it has the potential clear white spot lesions.…”
Section: Desensitizing Agentsmentioning
confidence: 99%